Tinjauan Yuridis Perlindungan Hukum Hak Cipta Digital terhadap Produk Aplikasi Digital di Perusahaan Startup - Andien Pradipta Kosasih; Asep Saripudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article discusses the legal protection of digital applications developed by startup companies in Indonesia, particularly in the context of copyright. Startups are business entities that rely on information technology and often produce copyright-protected creative works. However, the lack of legal awareness and sufficient understanding of copyright regulations can lead to confusion regarding copyright ownership and give rise to legal issues in the future. This research employs a normative legal research approach by analyzing relevant copyright regulations in Indonesia and studying cases related to the protection of copyright in digital applications. The analysis reveals that copyright protection is granted automatically according to the fundamental principles of copyright. However, startups need to strengthen their legal awareness of employment agreements that govern copyright ownership. Additionally, registering creative works and joining a collective management organization are recommended as measures that startups can take to effectively protect their copyrights. By following these recommendations, startups can avoid legal issues concerning copyright ownership and ensure adequate protection of their creative works. Legal awareness and a good understanding of copyright regulations are crucial for digital application developers to maximize their innovative potential in a competitive business environment in the era of the Fourth Industrial Revolution.